Effects of laser shock peening on the corrosion behavior and biocompatibility of a nickel–titanium alloy. Issue 6 (14th December 2018) - Zhang, Ruixia; Mankoci, Steven; Walters, Nicholas; Gao, Hongyu; Zhang, Hao; Hou, Xiaoning; Qin, Haifeng; Ren, Zhencheng; Zhou, Xianfeng; Doll, Gary L.; Martini, Ashlie; Sahai, Nita; et al.
Abstract: Nickel–titanium (NiTi) alloy is an attractive material for biomedical implant applications. In this study, the effects of laser shock peening (LSP) on the biocompatibility, corrosion resistance, ion release rate and hardness of NiTi were characterized. The cell culture study indicated that the LSP‐treated NiTi samples had lower cytotoxicity and higher cell survival rate than the untreated samples. Specifically, the cell survival rate increased from 88 ± 1.3% to 93 ± 1.1% due to LSP treatment. LSP treatment was shown to significantly decrease the initial Ni ion release rate compared with that of the untreated samples. Electrochemical tests indicated that LSP improved the corrosion resistance of the NiTi alloy in simulated body fluid, with a decrease in the corrosion current density from 1.41 ± 0.20 μA/cm 2 to 0.67 ± 0.24 μA/cm 2 . Immersion tests showed that calcium deposition was significantly enhanced by LSP. In addition, the hardness of NiTi alloy increased from 226 ± 3 HV before LSP to 261 ± 3 HV after LSP. These results demonstrated that LSP is a promising surface modification method that can be used to improve the mechanical properties, corrosion resistance and biocompatibility of NiTi alloy for biomedical applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1854–1863, 2019.